An Open-Label Clinical Study Evaluating the Therapeutic Effect of Lashuna Rasayana in Gridhrasi (Sciatica) - Dr. Anupama S; Dr. Sangeetha Toshikhane (The Bioscan, 2025)
In the daily clinical practice, Vatavyadhi is one of the most prevailing health problems and low back ache is one among them. Gridhrasi is one of the main causes for acute and chronic low back pain. Kandara or else termed as gridhrasi snayu is affected in gridhrasi causing ruja (pain) as the dominant feature. Snigdha sweda, virechana karma, niruha basti, anuvasana basti, agnikarma, siravyadha, shamana medications and rasayana form the complete treatment of gridhrasi in both the varieties with little difference. Treatment can be planned as Shamana Shodhana and Rasayana Chikitsa in Gridhrasi. Studies have shown that Rasayana Chikitsa helps in providing long term qualitative improvement in patients suffering from gridhrasi. Lashuna Rasayana is one such treatment modality wherein Vatavyadhi is being mentioned as an indication. Results showed that administration of Lashuna Rasayana is effective in the remission of the symptoms of Gridhrasi as evidenced by statistically significant reduction in the symptom score of various subjective and objective parameters.